Numerical investigation of the performance of RC beam-column connection using quench-tempered reinforcement steel bars - Viloria, Adrian D. (Animo Repository, 2021)
In the Philippines, reinforced concrete buildings using moment frames with infill walls (CHB) is the common practice in RC building design and construction. These structures are customarily reinforced with the ductile micro-alloyed (MA) rebars. However, quenched-tempered (QT) steel have penetrated the Philippine market decades ago, and have replaced the normally used MA steel as reinforcements. Studies have shown that QT steel is more likely to perform less in low cycle fatigue compared to MA steel, in which countries like Taiwan, Japan, United States of America, Canada, and New Zealand were reported to ban or put restrictions to its use. With the QT bar’s penetration into the market and its inevitable continuous use as reinforcements to concrete structures, there is a need to investigate and understand the performance and limitations of QT-reinforced concrete beam-column connections, a key-component in moment frames, to further provide a new set of guidelines, if any, and evaluate if existing codes are sufficient to retain structural integrity, hence, a numerical study is initiated. Simulations results suggest that the behaviour of QT as reinforcements brings minimal increase to the connection’s load capacity by about 19%, but with significant reduction in ductility index ranging from 7% to 69% and about 7 times more severe concrete cover spalling or joint failure. In parametric study, highest MCR shows 35% decrease in the beam’s ultimate load capacity but with 168% increase in ductility index and 96% decrease in the severity of joint failure, highest CAR shows 4% increase in ductility but with a 16% decrease in concrete cracks or failure localized at the joint area, highest BTRR exhibits 57% load capacity increase in the expense of 86% ductility reduction and 8 times more joint damage severity, and the highest LRBDR shows 12% increase in capacity but with decrease in ductility by 21% and 350% increase in concrete joint strain. Furthermore, higher MCR, lower CAR, lower BTRR, and lower LRBDR finite element models acquired concrete joint damages initially at 0.003 mm/mm. Additionally, the inclusion of joint stirrups contributed to the increase the structure’s general strength and toughness: slight increase to the beam load capacity by about 4%, increase in the structure’s ductility index by about 2% to 56%, and considerable decrease in concrete failure at the joint region by about 17% to 87%. It is then found out that the high yield strength of quench-tempered rebars is the primary cause of producing “stronger” beams, hence, the energy is transferred from the beam to the joint area; accumulation of concrete strains at higher values on the joint region occurs which further leads to more severe concrete cover spalling, damage, and total joint failure. Moreover, results suggest that in an earthquake event, concrete cracks manifest at the fixed-end beam region initially then propagate towards the joint region more rapidly in QT-employed connections, in contrast to MA-equipped connections. However, following the ACI 318-14 code for seismic detailing, QT-equipped beam-column connections show overall increase in performance: slight increase in the load capacity by 3%, significant increase in the ductility index by 29% to 77%, and remarkable decrease in concrete joint strain by 94%, all in which render moment frame resiliency against lateral loads. Also, with the use of acceptance criteria of performance level in ASCE 41, seismic-detailed QT-connection models were found to perform satisfactorily and better compared to basic ordinary models.